"Le système doit être mis à jour": Renforcer la protection contre le cyberharcèlement et contre la violence et le harcèlement fondés sur les TIC dans le monde du travail - Valerio De Stefano; Ilda Durri; Charalampos Stylogiannis; Mathias Wouters (Organisation internationale du Travail, 2020)
The term 'cyberbulling' has been used to describe aggressive conducts carried out through information and communication technologies (ICT), and can involve picture/video clips, emails, or social network sites, among others. Cyberbullying in the world of work is a relatively recent and unexplored phenomenon, despite the pervasive use of ICT in today's work environments and arrangements. The paper seeks to start filling this void, also in response to the newly adopted ILO Violence and Harassment Convention, 2019 (No. 190), and accompanying Recommendation (No. 206), that include in their scope violence and harassment occurring also "through work-related communications, including those enabled by information and communication technologies". This paper examines legal sources around cyberbullying in the world of work; reviews measures adopted across countries to counter bullying and discusses how they could be used to also address cyberbullying. It concludes with preliminary suggestions on possible ways to counter cyberbullying.
Keywords: 330; precarious employment; temporary employment; casual work; non-standard forms of employment; working conditions; labour contracts; bullying at work; sexual harassment; workers privacy; workplace violence; inequality; technology; information and communication technologies